Funções L homogênea e não homogênea em testes de hipótese de completa aleatoriedade espacial - Sousa, Sidcleide Barbosa de (2016)
The main aim of this work is to investigate the power of tests against the null hypothesis of complete spatial randomness in simulated point patterns that present both inhomogeneity and dependence. The tests use both the homogenous and inhomogeneous L functions on a Kolmogorov-Smirnov statistic. The results show that the homogeneous L function should not be used in patterns that is know or suspect to be spatially inhomogeneous and that the inhomogeneous L function should not be used in homogeneous patterns. The methods presented in this dissertation are applied in an actual spatially inhomogeneous pattern and the results corroborate the results from simulated data sets.